2015
DOI: 10.1097/aud.0000000000000137
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Impairment in Relation to Severity of Diabetes in a Veteran Cohort

Abstract: Objective Type 2 diabetes is epidemic among veterans, approaching three times the prevalence of the general population. Diabetes leads to devastating complications of vascular and neurologic malfunction and appears to impair auditory function. Hearing loss prevention is a major health-related initiative in the Veterans Health Administration. Thus, this research sought to identify, and quantify with effect sizes, differences in hearing, speech recognition, and hearing-related quality of life (QOL) measures asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 50 publications
2
31
1
1
Order By: Relevance
“…Effects of DM on hearing sensitivity have been widely reported. We and others have found that those with DM have poorer hearing than control participants without DM and that this difference in hearing is most apparent among those under the age of 50 – 60 years, before age-related changes begin to dominate (Frisina et al 2006; Vaughn et al 2005; Bainbridge et al 2008; Austin et al 2009; Bainbridge et al 2011; Konrad-Martin et al 2015; Horikawa et al 2013; Akinpelu et al 2014a). Combining data across multiple studies, a recent meta-analysis estimates the odds of having a hearing loss of 25 dB HL or greater among individuals with type 2 DM is roughly twice that observed among controls (OR 1.91; 95% confidence interval [CI] 1.47–2.49) (Akinpelu et al 2014a).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Effects of DM on hearing sensitivity have been widely reported. We and others have found that those with DM have poorer hearing than control participants without DM and that this difference in hearing is most apparent among those under the age of 50 – 60 years, before age-related changes begin to dominate (Frisina et al 2006; Vaughn et al 2005; Bainbridge et al 2008; Austin et al 2009; Bainbridge et al 2011; Konrad-Martin et al 2015; Horikawa et al 2013; Akinpelu et al 2014a). Combining data across multiple studies, a recent meta-analysis estimates the odds of having a hearing loss of 25 dB HL or greater among individuals with type 2 DM is roughly twice that observed among controls (OR 1.91; 95% confidence interval [CI] 1.47–2.49) (Akinpelu et al 2014a).…”
Section: Introductionmentioning
confidence: 65%
“…Significant effects of DM on pure tone thresholds and central ABR components are found more often than not upon investigation, however, there is substantial between-study heterogeneity in the findings (hearing and ABR: Akinpelu et al, 2014a; hearing: Horikawa et al 2013; Konrad-Martin et al 2015). There are a number of possible reasons for this.…”
Section: Introductionmentioning
confidence: 99%
“…There was no association of age with the absence of responses in the OAE. Some studies involving individuals with older age, observed the relation of DM with the hearing loss 14,18,23 and with the absence of OAE 2 , while others found no association 15,24 .…”
Section: Discussionmentioning
confidence: 99%
“…DM is epidemiologically associated with sensorineural hearing loss (4-6). The cochleae of humans and animals with DM manifest corresponding microangiopathic and neuroepithelial changes, including capillary basement membrane thickening in the stria vascularis, thickening and occlusion of cochlear arterioles and arteries, and variable degrees of cochlear hair cell and spiral ganglion cell loss (7, 8).…”
Section: Introductionmentioning
confidence: 99%